Acute Toxicity Of Heavy Metals (Cadmium Chloride, Chromium Trioxide And Lead Nitrate) And Their Effects On The Freshwater Prawn Macrobrachium Rosenbergii - R. SOWDESWARI; P. SARAVANA BHAVAN; P. ANANTHI (International Journal of Pharma and Bio Sciences, 2012)
The post larvae (PL) of Macrobrachium rosenbergii (2.5 cm and 0.15g) were subjected to static renewal type acute toxicity tests against cadmium chloride (CdCl2), chromium trioxide (CrO3) and lead nitrate (Pb(NO3)2). The 96 h LC50 values were calculated to be 58.93 µg/L, 2.08 mg/L and 25.97 mg/L for CdCl2, CrO3 and Pb(NO3)2 respectively. PL were exposed to the 96 h LC50 concentrations of these heavy metals for a period of 96 h to study their acute impacts on whole body concentrations of basic biochemical constituents, such as total carbohydrate, lipid, protein and amino acids, activities of metabolic enzymes, such as glutamate–oxaloacetate transaminase (GOT) and glutamate–pyruvate transaminase (GPT) and activity of enzymatic antioxidant, catalase. The levels of these biochemical constituents were found to be significantly (P<0.102 - 0.00) decreased in test prawns when compared with control. Among these heavy metals the recorded impact in contents of biochemical constituents was severe in test prawns that had been exposed to CdCl2, followed by Pb(NO3)2 and CrO3. These results indicated the fact that energy was utilized to mitigate the toxic stress induced through these heavy metals. The energy utilization percentage was found to be higher in lipid followed by carbohydrate and protein. The activities of GOT and GPT were found to be significantly (P<0.020 - 0.00) decrease in test prawns when compared with control. The percentage decrease in GOT and GPT was higher in prawns exposed to CdCl2, followed by Pb(NO3)2 and CrO3. Among these two enzymes, the impact was more on GPT than GOT. These results indicated the presence of metabolic disturbances in test prawn due to heavy metal toxicity. The activity of catalase was found to be significantly (P<0.020 - 0.00) elevated in test prawns when compared with control. Such an elevation was higher in CdCl2 followed by Pb(NO3)2 and CrO3. Therefore, elimination of oxidative stress was in operation in test prawns exposed to these heavy metals. The overall result of this acute exposure to lethal concentrations of these heavy metals indicates the fact that the test prawns were under metabolic disturbances and tried to eliminate the oxidative stress.